Design strategies using multi-criteria decision-making tools to enhance the performance of building façades. (July 2020) - Moghtadernejad, Saviz; Chouinard, Luc E.; Mirza, M. Saeed
Abstract: The climate change crisis and the need to control environmental impacts of the construction industry have motivated designers toward designing high performance and sustainable buildings. A building's façade, as a part of the enclosure, is certainly no exception to this requirement; however, despite the significant potential for building energy savings and reduction of environmental impacts, building façade design is not receiving proper attention. Presently, there is a need for a systematic approach to facilitate the integration of the various disciplines involved (e.g. architecture, as well as structural, mechanical and electrical design) and provide a comprehensive action plan that considers the life cycle stages of a façade system from conceptual design to demolition. This paper initially provides the required actions and considerations in each phase of design to provide a new and simplified guideline for designers in achieving a high performance façade system, with the help of Multi-Criteria Decision-Making (MCDM) methods. Secondly, the application of the Choquet integral and the Analytic Hierarchy Process (AHP) is discussed to select the most suitable alternatives in façade preliminary design for a case study building, and the results are compared. Highlights: Introducing a systematic approach for designing high performance building façades. Identifying necessary facade considerations during various life cycle stages. Identifying major performance attributes of building facades and the related quantification process. Application of Choquet integral in façade preliminary design stage. Avoid time-consuming and costly iterations related to façade design.